The Influence of Training, Empowerment, and Organizational Commitment on Employee Performance at PT Rachmat Jaya Sejati Gresik - Siti Sholihatun Mukaromah; I Putu Artaya (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2018)
The purpose of this study is to analyze training, empowerment, and organizational commitment on employee performance at PT Rachmat Jaya Sejati Gresik. This research is using quantitative methode. The population and sample are 35 employees at PT Rachmat Jaya Sejati Gresik. Data retrieval technique is by distributing questionnaires. In this study using SPSS version 16.0 software and multiple linear regression analysis. The results showed that training has a significant effect of 53.9% on the employee performance; empowerment has not a significant effect of 11.8%; organizational commitment has a significant effect of 36.7%. In simultaneous, training, empowerment, and organizational commitment had a significant effect of 94%. so, there are a number of suggestions for companies to maintain and improve organizational training and commitment. Especially for empowerment, companies must improve empowerment such as more involving and paying attention to employee opinions in solving problems.